2012
DOI: 10.1242/jcs.103648
|View full text |Cite
|
Sign up to set email alerts
|

Toxofilin upregulates the host cortical actin cytoskeleton dynamics facilitating Toxoplasma invasion

Abstract: SummaryToxoplasma gondii, a human pathogen and a model apicomplexan parasite, actively and rapidly invades host cells. To initiate invasion, the parasite induces the formation of a parasite-cell junction, and progressively propels itself through the junction, inside a newly formed vacuole that encloses the entering parasite. Little is known about how a parasite that is a few microns in diameter overcomes the host cell cortical actin barrier to achieve the remarkably rapid process of internalization (less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 32 publications
3
58
0
1
Order By: Relevance
“…26 It has been previously shown that Toxoplasma tachyzoites secret Toxofilin, an actin-binding protein which upregulates actin turnover, increasing depolymerization of the filaments on the area of invasion, facilitating T. gondii internalization. 27 It was previously shown that another protozoan parasite, Giardia intestinalis, which colonizes and causes intestinal disease, also induces disorganization of the apical F-actin cytoskeleton in Caco-2 monolayer in an adhesion-dependent manner, leading to the impaired distribution of functional brush border-associated proteins. 28 The binary toxin, Clostridium difficile transferase, induces actin depolymerization that alter the microtubule and endoplasmic reticulum organization, Whole cell lyses were separated on SDS-PAGE gel and immunoblotted with antibodies against the corresponding tight junction proteins, ZO-1, occludin, and claudin-1, followed by chemiluminescence detection.…”
Section: Discussionmentioning
confidence: 99%
“…26 It has been previously shown that Toxoplasma tachyzoites secret Toxofilin, an actin-binding protein which upregulates actin turnover, increasing depolymerization of the filaments on the area of invasion, facilitating T. gondii internalization. 27 It was previously shown that another protozoan parasite, Giardia intestinalis, which colonizes and causes intestinal disease, also induces disorganization of the apical F-actin cytoskeleton in Caco-2 monolayer in an adhesion-dependent manner, leading to the impaired distribution of functional brush border-associated proteins. 28 The binary toxin, Clostridium difficile transferase, induces actin depolymerization that alter the microtubule and endoplasmic reticulum organization, Whole cell lyses were separated on SDS-PAGE gel and immunoblotted with antibodies against the corresponding tight junction proteins, ZO-1, occludin, and claudin-1, followed by chemiluminescence detection.…”
Section: Discussionmentioning
confidence: 99%
“…It is secreted by the rhoptries and is involved in host cell invasion [62,63]. Toxofilin is known for its ability to bind to parasite and mammalian actin and for its role in the regulation of actin filament disassembly and turnover [64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…Blots were scanned with an Odyssey Infrared Imaging System (Li-COR Biosciences, Courtaboeuf, France), and images were processed with ImageJ software (28). For IFA, parasites growing in HFF cells for 24 to 32 h were stained with B3.90 anti-AMA1 (19) and anti-toxofilin (29) antibodies after fixation with paraformaldehyde (PFA) (2% in PBS). Peritoneal cells were fixed and subjected to Triton X-100 permeabilization before being incubated with anti-GRA3 antibodies (1/300 dilution) and with anti-F4/80-PE antibodies (1/100 dilution).…”
Section: Methodsmentioning
confidence: 99%